SOVEREIGNTY, VIOLENCE, AND INJUSTICE: AN EXAMINATION OF THE NATION-STATE AS THE BASIS OF THE GLOBAL WORLD ORDER - Hernandez, Michael Roland (Lembaga Penelitian dan Pengabdian Masyarakat (LPPM) STPAK St. Yohanes Penginjil Ambon, 2025)
The traditional notion of sovereignty consists of the idea of an absolute, indivisible power possessed by the state enabling it to regulate its own affairs, achieve the purposes for which it was created and to safeguard its own integrity. Today, however, the triumph of economic globalization and the independence of capitalist production and exchange from political control have contributed to what is perceived as the decline of the nation-state. In this regard, this paper will be concerned with the concept of sovereignty as it is exercised by nation-states. Given this connection between sovereignty, violence and injustice, this paper argues that violence is an essential constitutive element of sovereignty.